Editorial: blockchain technology implications for international business research and practice - Šilenskytė, Aušrinė; Sinkovics, Rudolf R.; Kuivalainen, Olli (Inderscience publishers, 2025)
Blockchain technology has been recognised as a potentially transformative force in international business (IB), drawing increasing interest from both practitioners and academics. Although a growing body of outputs on blockchain highlights its unique features, such as transparency, immutability, decentralisation, and peer-to-peer transactions, most studies remain descriptive, focusing on specific applications, such as cryptocurrencies and smart contracts. This special issue aims to move beyond such descriptive analyses by examining how blockchain technology aspects such as its type intersect with critical IB themes, such as trust, institutional environments, agency, and sustainability. It argues that to fully understand the impact of blockchain on business practice, sustainability, and government responses, technological aspects have to be introduced into discussions. This editorial offers a framework for assessing blockchain research in IB, proposes a research agenda emphasising the technology’s unique characteristics, and explains how the contributions in this issue provide a more comprehensive view of blockchain’s opportunities and limitations.
Keywords: governance and trust; digital platforms and ecosystems; GVCs; global value chains; DAOs; decentralised autonomous organisations; sustainability and circular economy; fi=Strateginen johtaminen|en=Strategic Management|